Eco Tourism in Telangana State - Dr. B. Sandhya Rani (Eduzone: International Peer Reviewed/Refereed Multidisciplinary Journal, 2022)
Earth was formed 46 billion years ago; the planet gives us resources to build our houses. There are many things our mother earth gives to appreciate the land scape, the culture, Awesome Nature, etc. We should never take it granted. Travelling is the best way to explore magic of the world, to experience cultures; however damage and waste occur because of the inappropriate behaviours of travelers. Tourism is travel for pleasure. And this is the theory and practice of travelling and entertaining, accommodating tourists. Eco tourism involves visiting undisturbed natural areas. This is small scale alternative to standard commercial mass tourism. It includes land scape, culture, and awesome nature. Eco tourism educates people to appreciate our environment. Eco tourism is Responsible travel to National and cultural areas that conserves the environment and sustain the well being of local people. In Telangana, every place has a story for us, every movement is an experience for us. Glorious legacy of dynasties lakes, wild life adventures, forts, unique festivals, tribal art forms, cultures.